New Tauberian theorems for statistical Cesàro summability of a function of three variables over a locally convex space - Granados, Carlos; Das, Ajoy Kanti (Armenian Journal of Mathematics, 2022)
In this paper, we prove two new Tauberian theorems via statistical Cesàro summability mean of a continuous function of three variables by using oscillating behavior and De la Vallée Poussin means of a triple integral over a locally convex space. Moreover, some remarks and corollaries are provided here to support our results.